Avoiding the Swine: A Hedonist’s Dilemma - Won Choi, Jee (Stance: an international undergraduate philosophy journal, 2021)
What constitutes a good life? A hedonist’s answer to this question is rather simple— more pleasure, less pain. While hedonism was previously a widely accepted belief, it now suffers from several crucial objections. A challenge particularly vexing to hedonists is the Philosophy of Swine: could it be possible that our lives may be less than that of a theoretical swine? In this essay, I argue that lifetime hedonism, the view of hedonism concerned with one’s total lifelong well-being, does not survive this objection. In particular, I will refute the counterarguments that modern-day hedonist, Ben Bramble, presents against the Philosophy of Swine objection.